PENGARUH BUDAYA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR ISLAM NEGERI DI KOTA METRO - Sevi Lestari; Yuli Supriani (IAI AGUS SALIM METRO LAMPUNG, 2022)
The teacher is asked to be able to create an atmosphere of learning that emphasizes the occurrence of active student learning through various activities. The purpose of this study was to determine the influence of school culture toward teachers’ performance in State Islamic Elementary School in Metro City. This study uses a quantitative approach with nonexperimental design. The population in this study were teachers in the State Islamic Elementary Schools in Metro City. Based on teacher data and formulated using Slovin technique, The instrument used in this study was a questionnaire. Before the instrument is used, first tested the validity and reliability. Data collection techniques using test methods and data analysis techniques using correlation techniques. Based on the result of regresion test, score of school culture is as high as score of teacher’s performance. It menas that school culture gives positive effect to tescher’s performance. So, it can be concluded that school culture gives positif effect to teacher’s performance in state Islamic school of Metro.